PENGARUH KOMBINASI LUMPUR MERAH DAN PUPUK KANDANG AYAM TERHADAP KETERSEDIAN HARA N, P, K DAN PERTUMBUHAN TANAMAN JAGUNG PADA TANAH ALUVIAL - Sempurna, Bayu; Suswati, Denah; Chandra, Tino Orciny (Agros Journal of Agriculture Science, 2024)
Hybrid corn (Zea mays.) is the main food commodity cultivated after rice. The use of alluvial soil for planting hybrid corn concerns the physical, chemical and biological properties of the soil, because the soil structure is poor, it is massive, low pH, minimal nutrients and C-Organic is soil that has just undergone development and has a high ground water level. The research aims to determine the effect of a combination of red mud and chicken manure on the availability of N, P, K nutrients and the growth of corn plants in Alluvial Soil. This research used a Completely Randomized Design (CRD) with 9 treatments, namely, A1(100 g red mud + 1 kg chicken manure), A2(100 g red mud + 2 kg chicken manure), A3(100 g red mud + 3 kg chicken manure), A4(200 g red mud + 1 kg chicken manure), A5(200 g red mud + 2 kg chicken manure), A6(200 g red mud + 3 kg chicken manure), A7(300 g red mud + 1 kg chicken manure), A8(300 g red mud + 2 kg chicken manure), A9(300 g red mud + 3 kg chicken manure). The results of this study showed that treatment, A6 (200 g red mud + 3 kg chicken manure) could increase soil pH, organic carbon, total nitrogen, available phosphorus, and exchangeable potassium, plant height and stem diameter by 25.88% - 112, 78%.